Opportunities to Increase Product Export Power Through Development of Fruit and Vegetable Industry in Uzbekistan - Dilsaboxon Rustamova Djuraevna (Genius Journals, 2022)
This article contains recommendations for the sustainable development of the fruit and vegetable industry in the processing and storage of fruit and vegetables in the Republic of Uzbekistan, as well as suggestions for further support of the industry
Keywords: Fruit and vegetables; fruit and vegetable export; cluster; cooperation